Evidentiranje likovno nadarjenih učencev v osnovni šoli - Duh, Matjaž (Revija za elementarno izobraževanje, 2008)
In the article we discuss how artistically talented pupils are identified in Slovenian primary schools. The identification of artistically talented pupils was conducted through observation and evaluation of their artwork. In the research we wanted to know how primary school teachers perceive the talent of artistically gifted pupils. In the discussion we established that in Slovenia we still do not have a systematic way of observing pupils with above-average abilities in visual art as we do in other areas of primary education. It was determined that identifying artistically talented pupils represents a demanding task for teachers. The goal of our research, which included 63 pupils that had been identified by teachers as artistically talented, was to determine whether these pupils really have talent or not. The results show that teachers often do not have adequate abilities in recognizing the signs of potential artistic talent.
Keywords: likovna vzgoja; nadarjeni učenci; nadarjenost; osnovne šole